Moving the Field Forward with Empathy, Engagement, Equity, and Ethics. (3rd September 2022) - Meyer, Seth J.; Johnson, Richard Greggory; McCandless, Sean
Abstract: In the previous introduction to this special issue, we presented the new 4Es, empathy, equity, engagement, and ethics. These 4Es represent an evolution in public administration, replacing economy, efficiency, and effectiveness as central pillars of the field. Through these 4Es, we propose a movement towards a more equitable public administration, which meets the needs of the future of public administration. In this introduction to the second part of this special issue, we explore the research and teaching implications of the 4Es. Through this discussion and along with our articles in this special issue, we provide guidance on the use of the 4Es in public administration teaching, education, and practice.